Internal dynamic between dividend policy and environmental, social, and governance (ESG) performance among listed companies in the United States - Ang, Sin Yu; Ho, Shi Cheng; Hong, Sze Yin; Lee, Yi Seng (2024)
This research has the purpose of investigate the internal dynamic between dividend yield and environmental, social and governance (ESG) performance among listed companies in United States. The explanatory variables include ESG score, Sales Growth, Leverage, Price-to-Book Ratio, and Return on Asset. The dividend signalling theory and stakeholder theory will be the fundamental theories of this study to examine how explanatory variables will affects dividend yield. The secondary data within year 2013 to 2021 are obtained from Refinitiv Eikon Database. A total of 87 companies are selected as sample for this research. To explore the interplay between dividend yield and environmental, social, and governance (ESG) performance among listed companies in the United States, panel data analysis will be employed. Initially, panel unit root tests are conducted, followed by the application of Pooled Ordinary Least Squares (POLS), Fixed Effects Model (FEM), and Random Effects Model (REM). To determine the most suitable model, Poolability F-Test and Hausman Test are being utilized. Additionally, diagnostic checks for multicollinearity, heteroscedasticity, and autocorrelation are performed to identify any underlying economic issues within the model. This study indicates that ESG Score, Sales Growth, Leverage, Price-to Book Ratio, and Return on Asset have significant influence on dividend yield.